Oxygen diffusivity mapping of fruit and vegetables based on X-ray CT. (October 2021) - Nugraha, Bayu; Verboven, Pieter; Janssen, Siem; Hertog, Maarten L.A.T.M.; Boone, Matthieu; Josipovic, Iván; Nicolaï, Bart M.
Abstract: Oxygen (O2 ) diffusion affects respiration of fruit and vegetables and, thus, their behavior under controlled or modified atmosphere storage conditions. Effective gas diffusivity expresses, at a macroscopic level, the overall ability of the tissue to exchange gasses and is determined by the porous structure of the tissue. Variations of the tissue microstructure across the fruit and vegetable organs may result in an effective O2 diffusivity that is position dependent. A method was developed to create three-dimensional (3-D) effective O2 diffusivity maps in fruit and vegetables based on low resolution X-ray computed tomography (CT) images. The effective tissue diffusivity was first calculated for representative small tissue samples of eggplant, turnip, apple, and pear fruit, using microscale diffusion simulations with a finite volume model on high resolution CT images, which served as ground truth. Then the dependence of the effective O2 diffusivity on the total and open porosity and tortuosity of the samples was investigated. The regression model of the diffusivity with respect to total porosity had an RMSE = 6.90 × 10 −7  m 2  s −1 and R 2  = 0.92, while that with respect to open porosity had an RMSE = 5.41 × 10 −7  m 2  s −1 and R 2  = 0.95, for all samples and organs. The incorporation of the pore network tortuosity did not improve the goodness of fit of the correlation. The correlation based on total porosity was found sufficient for eggplant and turnip that has a large porosity, while diffusivity profiles in apple and pear fruit correlated better with the open porosity due to the presence of disconnected (closed) pores in these fruits that contribute less to the effective diffusion. Thereto, open porosity was estimated from a correlation model between total porosity and open porosity with RMSE = 5.76% for apple and RMSE = 0.93% for pear. Porosity profiles of organs computed from low resolution CT grayscale images were translated to O2 diffusivity profiles using the correlation model and tested against the high resolution ground truth values. Finally, effective diffusivity maps were created for intact organs, which for the first time provides insight in the spatial variation in gas exchange capability of different plant species. Highlights: Effective O2 diffusivity in an intact product was mapped based on X-ray CT. Diffusivity models were developed based on total and open porosity, and tortuosity. O2 diffusivity of fruit and vegetables was found heterogeneous.